Adverse Outcomes After Hospitalization and Delirium in Persons With Alzheimer Disease - Fong, Tamara G. (2012)
BACKGROUND: Hospitalization, frequently complicated by delirium, can be a life-changing event for patients with Alzheimer disease (AD). OBJECTIVE: To determine risks for institutionalization, cognitive decline, or death associated with hospitalization and delirium in patients with AD. DESIGN: Prospective cohort enrolled between 1991 and 2006 into the Massachusetts Alzheimer’s Disease Research Center (MADRC) patient registry. SETTING: Community-based. PARTICIPANTS: 771 persons aged 65 years or older with a clinical diagnosis of AD. MEASUREMENTS: Hospitalization, delirium, death, and institutionalization were identified through administrative databases. Cognitive decline was defined as a decrease of 4 or more points on the Blessed Information-Memory-Concentration test score. Multivariate analysis was used to calculate adjusted relative risks (RRs). RESULTS: Of 771 participants with AD, 367 (48%) were hospitalized and 194 (25%) developed delirium. Hospitalized patients who did not have delirium had an increased risk for death (adjusted RR, 4.7 [95% CI, 1.9 to 11.6]) and institutionalization (adjusted RR, 6.9 [CI, 4.0 to 11.7]). With delirium, risk for death (adjusted RR, 5.4 [CI, 2.3 to 12.5]) and institutionalization (adjusted RR, 9.3 [CI, 5.5 to 15.7]) increased further. With hospitalization and delirium, the adjusted RR for cognitive decline for patients with AD was 1.6 (CI, 1.2 to 2.3). Among hospitalized patients with AD, 21% of the incidences of cognitive decline, 15% of institutionalization, and 6% of deaths were associated with delirium. LIMITATIONS: Cognitive outcome was missing in 291 patients. Sensitivity analysis was performed to test the effect of missing data, and a composite outcome was used to decrease the effect of missing data. CONCLUSION: Approximately 1 in 8 hospitalized patients with AD who develop delirium will have at least 1 adverse outcome, including death, institutionalization, or cognitive decline, associated with delirium. Delirium prevention may represent an important strategy for reducing adverse outcomes in this population. PRIMARY FUNDING SOURCE: National Institute on Aging and the MADRC.